Comunidade de formigas subterrâneas em área de pastagem nativa na região central do Rio Grande do Sul - Santos, Isis Caroline Siqueira (2020)
The Pampa biome is formed by an ecosystem with high biodiversity of both fauna and flora represents more than 60% of the territory of Rio Grande do Sul state. As a rural environment the main activity developed is agriculture and livestock, which develops strongly in that state. This activity is mainly characterized by extensive cattle raising, using the native resources of native fields for animal feed. However, this activity, when handled poorly, promotes soil degradation, driven by the excessive animal load in these areas and also coupled with the lack of knowledge of the dynamics of this environment. Consequently, the lack of proper management, causes changes in soil properties, thus directly affecting the associated fauna. For monitoring these areas, arthropods, especially ants, can be used as excellent bioindicators of these changes in the environment. Thus, the objective of this work was to know the fauna of underground ants in a native pasture area with grazing management. The study was carried out in a native pasture area belonging to the Federal University of Santa Maria and located in the physiographic region of the Central Depression of Rio Grande do Sul. The treatments of the area were two grazing intervals defined by thermal sums of 375 and 750 degree-days (GD) that determine livestock management and an exclusion area on the border of the two treatments. The mini-Winkler methodology was used to collect biological material. In total 180 points were sampled and distributed in 45 plots. 64 ant species belonging to 19 genera and five subfamilies were obtained. The largest occurrence of ants was of the genera Pheidole Westwood, 1839, Wasmannia Forel, 1893, Solenopsis Westwood, 1840, Brachymyrmex Mayr, 1868 Hypoponera Santschi, 1938 and Typhlomyrmex Mayr, 1862. Of the 64 species of ants collected in the native pasture area, he observed only 14 species are indicative of the grassland area and all species from the exclusion area. Species richness showed a significant difference between the sampled areas, but the exclusion area showed greater richness. It was also found that the elements Al3+, S and pH directly influenced the richness of underground ant species. The species composition did not differ between treatments (375 and 750 GD), however, there was a difference in the grazing exclusion area, with some species being related to soil nutritional elements. The inclusion of cattle in native pasture areas reduces the richness and composition of underground ant species.